KETERSEDIAAN DAN PEMANFAATAN MEDIA KOMPONEN INSTRUMEN TERPADU (KIT) IPA DI SD NEGERI KECAMATAN NANGGALO KOTA PADANG - Angreni, Siska; Sari, Rona Taula (JURNAL PENDIDIKAN DASAR NUSANTARA, 2017)
This study aimed to analyze the availability and utilization of media components Integrated Instrument in science teaching in elementary schools throughout the District Nanggalo. The method used is descriptive method with survey forms. Instruments used observation sheets, questionnaires and interview guides. The results of the study science components Integrated Instrument media availability at the elementary school districts Nanggalo already sufficient for use in the learning process, with the condition science components Integrated Instrument media for use in learning is not damaged. As for the utilization of science components Integrated Instrument media in Elementary School District of Nanggalo not maximized in learning. Factors why teachers do not use science components Integrated Instrument media due to lack of teachers' skills in using these media.